Knowledge of Human Papilloma Virus Self-sampling and Cervical Cancers Screening Uptake among Gynaecology Clinic Attendees in a Tertiary Hospital in Nigeria (2023)
Cervical cancer remains a significant contributor to global cancer-specific morbidity and mortality, despite being one of the most preventable and treatable cancers. Uptake and knowledge of cancer screening has remained low in developing countries. Therefore, this study investigated the level of knowledge Human Papilloma Virus (HPV) Self-sampling and Cervical cancers screening uptake among gynaecology clinic attendees in Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. A cross-sectional design was employed in the study. A total of 256 respondents were selected using simple random sampling technique from two tertiary institutions in Osun State, Nigeria. A semi-structured questionnaire was used to collect data on the knowledge of HPV Self-sampling and cervical screening uptake from the respondents. Data were analysed and presented in percentages and association between variables were tested with logistic regression, chi-square and fisher’s exact test at 0.05 level of significance. The mean age of the respondents was 35.8±9.7 years, age of sex initiation for almost half (48.2%) of the respondents was between 21 and 25 years. Also, 66% of the respondents had not been screened of cervical cancer and 62.9% do not have enough education on self-sampling. However, 75.4.0% had poor knowledge on HPV self-sampling while 21.5% believed only sexually active women can only engage in self-sampling. There was a significant association between socio demographic, utilisation and knowledge of self-sampling for HPV. The study revealed poor knowledge on Human Papilloma Virus self-sampling and low screening uptake. Therefore, there is a need to strengthen the self-sampling knowledge among women for future screening.